Stereoselective Synthesis of 4-O-Tosyltetrahydropyrans via Prins Cyclization Reaction of Enol Ethers - Sarkar, Sujit; Devi, Namita; Porashar, Bikoshita; Ruidas, Santu; Saikia, Anil K (SynOpen, 2019)
Intramolecular cyclization of enol ethers mediated by para-toluenesulfonic acid leads to substituted tetrahydropyrans in good to moderate yields. The reaction is diastereoselective.
Keywords: tosyl tetrahydropyrans; Prins reaction; enol ether; cyclization; heterocycle